Removal of anionic dyes using activated carbon derived from Swietenia macrophylla shells grafted graphene oxide - Dharmendra, Godaba; Sahoo, Jitendra Kumar; Tripathy, Mausumi Priyanka; Choudhury, Deeptimayee (Separation science and technology, 2025)
Several studies have been conducted on the adsorption of dyes in the literature using activated carbon prepared from plant residues. The study of the removal of dyes from wastewater using Swietenia macrophylla shells modified with graphene Oxide (GO) has not been studied yet. In the current study, we prepared a low-cost and highly efficient adsorbent that is activated carbon (AC), mainly derived from Swietenia macrophylla shells then modified with GO, a promising sorbent for eliminating Congo Red (CR), Natural Red (NR) and, Eriochrome Black T (EBT) dyes from aqueous media. Then, the prepared GO/AC materials were analyzed by FT-IR, XRD, FE-SEM, EDX, EDS, Raman spectra and BET isotherm analysis. The isotherm and kinetic data were highly fitted to Langmuir isotherm model and Pseudo-second-order kinetic model, implying that the adsorption process is monolayer and chemisorptions, respectively. The maximum adsorption capacity for CR dye was 45.4 mg/g, EBT was 55.8 mg/g and Natural Red dye was 54.6 mg/g. The GO/AC material was further investigated by a reusability study in five cycles to check the efficiency of the adsorbent and the adsorption mechanism was studied for above three anionic dyes.